Application Of A Polymer-Based Sealing Material To Prevent Roof From Weathering - Peter Zhang (International Conference on Ground Control in Mining, 2009)
The immediate roof at the test site consisted of laminated clay shale that is likely to be susceptible to weathering. With seasonal dry-wet cycles in the mine ventilation air, the roof in the intake air would deteriorate and lose integrity over time. In many instances, the weathering-prone roof would gradually scale off piece by piece between bolts and over the entry corners. In some long-term entries, roof weathering could develop up to 2-3 ft deep with columns of bolted roof hanging under the upper intact roof. If wire mesh is used, the roof bags down and reduces the entry height, and the weight of the bagged roof tends to pull the bolts out and poses a safety hazard. An effective measure is always sought to support this type of weak roof that is sensitive to moisture degradation. One solution is to seal the roof shortly after entry development to prevent moisture penetration so that roof integrity can be maintained for the long term. In this application, a polymer-based sealing material was tested in the Rockspring mine for weathering protection and reinforcement. The material is a one-component polymer powder for spray application onto the roof and rib. The sealant material is mixed with water in the spraying nozzle to apply to the roof and rib as a paste. The product sets within 5-10 minutes and forms a membrane as thin as about 1/8-in. The membrane will quickly develop tensile and bonding strength within minutes and completely cure within a few days. Through sealing, bonding and lateral reinforcement, the integrity of the weak roof can be maintained. The material has been tried in a long-term evaluation over several months in a set of main entries in the Rockspring mine owned and operated by Rockspring Development, Inc., affiliate of Foundation Coal. Preliminary evaluation has shown that the material is an effective and economical solution to ensuring the long-term stability of weathering-prone roof.